School subject departments as sites for science teachers learning pedagogical content knowledge - McNicholl, J; Childs, A; Burn, K (2013)
This paper reports a study that explored science teacher learning of pedagogical content knowledge and the factors that facilitated this in their workplace, schools. The research design employed interview and observation in two secondary school science departments in England. A seven part construct of PCK was used to analyse all data and the findings indicated that, routinely, teachers collaborated in social settings to share knowledge, principally in relation to two areas of PCK, subject matter and teaching strategies and resources. The main resources teachers drew on were colleagues as well as a key material artefact, shared teaching schemes. While recognising our view of PCK does not abandon the idea of teacher knowledge as being individually stored and applied, rather the argument here is that school science is now so broad, complex and context-dependent that much of it needs to be off-loaded onto material artefacts and distributed amongst teachers. There are practical implications of this study for both ITE and CPD programmes in shifting the focus away from individualistic provision far removed from teachers' workplaces to that which works in the school context and at the department level where teachers are able to benefit from, and contribute to, shared knowledge and expertise therein. © 2013 © 2013 Teacher Development.